Introducing nitrogen atoms to amidoalkylindoles: potent and selective cannabinoid type 2 receptor agonists with improved aqueous solubility. Issue 12 (18th November 2019) - Ji, Yue-Yang; Wang, Zhi-Long; Pei, Fang-Ning; Shi, Jun-Jie; Li, Jiao-Jiao; Gunosewoyo, Hendra; Yang, Fan; Tang, Jie; Xie, Xin; Yu, Li-Fang
Abstract : Previously we identified a series of amidoalkylindoles as potent and selective CB2 partial agonists. Abstract : Previously we identified a series of amidoalkylindoles as potent and selective CB2 partial agonists. In the present study, we report our continuous effort to improve the aqueous solubility by introducing N atoms to the amidoalkylindole framework. Synthesis, characterization, and pharmacology evaluations were described. Bioisosteric replacements of the indole nucleus with an indazole, azaindole and benzimidazole were explored. Benzimidazole 43 (EC50, CB1 = NA, EC50, CB2 = 0.067 μM) and azaindole 24 (EC50, CB1 = NA, EC50, CB2 = 0.048 μM) were found to be potent and selective CB2 receptor partial agonists, both with improved aqueous solubility.